Subcellular localization and tissue expression pattern of SlMAPK7 gene in tomato - Guan Xiaoyan; Chen Lifei; He Yanjun; Wang Jie; Lu Gang (浙江大学学报. 农业与生命科学版)
Mitogen-activated protein kinase (MAPK) cascades are universal signal transmission modules in eukaryotes. Recent increasing evidences have proved that MAPKs play pivotal roles in plant growth and development, as well as in response to biotic and abiotic stresses. Up to date, a number of MAPK genes have been isolated from different plants. However, the most extensively studied MAPKs are MAPK3, MAPK4 and MAPK6 in Arabidopsis and rice. The function of other MAPK family members is not clear yet. Tomato, one of the most important vegetables, is considered one of the model plants for productive development. To the best of our knowledge, the research on tomato MAPK family genes is very limited. Therefore, this study aimed to characterize the temporal and spatial expression profiles of tomato SlMAPK7, analyze the cis-elements in its promoter sequences, and to confirm the subcellular localization of SlMAPK7 protein.The expression profiles of SlMAPK7 in the roots, stems, leaves, calyxes, petals, stamens, pistils, and fruits from flowering tomato plants were characterized by real-time fluorescent quantitative reverse transcription polymerase chain reaction (qRT-PCR), as well as the flower buds ranging from 2 mm to 8.5 mm in length, representing in different floral development periods. The 5′-upstream cis-acting sequences of tomato SlMAPK7 gene were identified by PCR method according to the tomato genome sequence data. PLACE and PlantCARE were used to analyze the cis-element of promoter. A plant expression vector with yellow fluorescent protein (YFP) was constructed to confirm the subcellular localization of SlMAPK7 protein. Meanwhile, another plant expression vector with green fluorescent protein and β-glucuronidase (GUS) report gene was constructed to study the activity of promoter. The promoter expression vector was transferred into Arabidopsis by Agrobacterium tumefaciens to analyze the promoter profiles.The expression analysis using qRT-PCR showed that the relative gene expression level of SlMAPK7 in stamen was far higher than other tissues. At different floral development stages, the highest gene expression level of SlMAPK7 was found in the flower bud with the length of 4.6-6.5 mm. Transient expression analysis indicated that YFP-SlMAPK7 fusion protein was localized in the cell nucleus and the membrane of onion epidermal cells. The 1 823 bp region flanking (from -29 bp to -1 851 bp) sequences of the 5′-upstream in the tomato SlMAPK7 gene were isolated and sequenced. Structure analysis of the promoter using PLACE and PlantCARE revealed that the promoter sequences contained basic cis-elements, such as TATA-box and CAAT-box and many abiotic stress responsive elements. It was worth noting that the sequences also contained several pollen development-related cis-elements. Transient expression analysis indicated that the cloned sequences were active promoters. The expression analysis of SlMAPK7 promoter in Arabidopsis by β-glucuronidase (GUS) staining showed that the SlMAPK7 was mainly expressed in apical meristem of stem and root during the seedling period, while it was expressed in stigma and receptacle in the adult plant.In conclusion, SlMAPK7 takes part probably in the signal transduction pathway in the cell nucleus and membrane, which may play an important role in the flower development in tomato. Our study provides some helpful informations for further elucidating the precise roles of MAPK7 in tomato growth and development.